Credit constraints in low density regions: microcredit in Alentejo - Rego, Conceição (2012)
Regions of low demographic and economic density face major development challenges that greatly increase the struggle of local productive agents for subsistence. In such areas, domestic policies have traditionally been more focused on subsidising the less favoured than in bridging the gap between the poor micro entrepreneurs and the financial funds. Notwithstanding this, inspired by the Bangladeshi experience, many microcredit projects have been implemented around the world and became instrumental tools to eradicate poverty and social exclusion. There are, however, various microfinance models, applied in diverse social and economic contexts, and involving distinct micro entrepreneurs’ profiles. In this work, we characterise the model implemented in Portugal and assess the level of development of one of its less favoured regions, Alentejo, from the point of view of microcredit. The analysis is performed with the objective of evaluating the strategy adopted and to identify the possible areas of improvement, in order to maximise the potential gains from microcredit.